2008
DOI: 10.1177/0954008308089710
|View full text |Cite
|
Sign up to set email alerts
|

POSS-Polyimide Nanocomposite Films: Simulated Hypervelocity Space Debris and Atomic Oxygen Effects

Abstract: The combined effect of hypervelocity space debris impact and atomic oxygen (AO) attack on the degradation of reinforced polyhedral oligomeric silsesquioxanes (POSS)-polyimide films was studied. A laser-driven flyer (LDF) system was used to accelerate aluminum flyers to impact velocities of up to 3 km s -1. The impacted films were exposed to an RF-plasma source, which was used to simulate the effect of AO in the low Earth orbit. Scanning electron microscopy (SEM) was used to characterize the fracture morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…The following amendment for the simulation of atomic oxygen erosion was employed based on the empirical equation and the reported experimental results [21,[25][26][27]: (1) No interaction occurs between POSS and atomic oxygen under high atomic oxygen fluence since the impact energy is not able to break the bond of POSS. (2) Heat reaction will not occur between atomic oxygen and composite as POSS absorbs the impact energy produced by atomic oxygen (3) according to relevant references [16,26,28], the erosion yields for 3% and 10% POSS/PVDF are = 1.24 × 10 −25 cm 3 /atom and = 0.8 × 10 −25 cm 3 /atom, respectively.…”
Section: Simulation Results Of Atomic Oxygen Erosion Of Poss/pvdf Commentioning
confidence: 99%
“…The following amendment for the simulation of atomic oxygen erosion was employed based on the empirical equation and the reported experimental results [21,[25][26][27]: (1) No interaction occurs between POSS and atomic oxygen under high atomic oxygen fluence since the impact energy is not able to break the bond of POSS. (2) Heat reaction will not occur between atomic oxygen and composite as POSS absorbs the impact energy produced by atomic oxygen (3) according to relevant references [16,26,28], the erosion yields for 3% and 10% POSS/PVDF are = 1.24 × 10 −25 cm 3 /atom and = 0.8 × 10 −25 cm 3 /atom, respectively.…”
Section: Simulation Results Of Atomic Oxygen Erosion Of Poss/pvdf Commentioning
confidence: 99%
“…As is reported, polyimide coated with TiO 2 or SiO 2 has exhibited superior AO resistance than unprotected one [3,16]. However, inherent and hypervelocity debris-induced defects within the coating will permit AO attack of the underlying polymer, although the SiO 2 coating itself is highly resistant to AO [17]. Therefore, rational design focusing on the molecular modification of polymeric materials, other than coating technology, is the key to manufacture new polyimides with desirable AO resistance.…”
Section: Introductionmentioning
confidence: 90%
“…The new macro-hole formation is a result of a multistep process that includes the establishment of a field of residual tensile stresses within the polymer due to the hypervelocity impact. 32 In addition, an increase in the polymer's local free volume occurs, 34 leading to increased molecular and AO diffusion into the polymer. Consequently, a local increase in the AO-induced erosion rate takes place, [35][36][37] resulting in the formation of new macro-holes.…”
Section: Synergistic Effect Of Hypervelocity Impacts and Atomic Oxygementioning
confidence: 99%
“…It was suggested that due to the hypervelocity impact, a residual tensile stress field is developed within the polyimide. 32,33 A model was proposed to explain the extensive erosion and the formation of the new holes in the impacted polyimide film due to AO exposure in the oxygen radio frequency plasma. The new macro-hole formation is a result of a multistep process that includes the establishment of a field of residual tensile stresses within the polymer due to the hypervelocity impact.…”
Section: Synergistic Effect Of Hypervelocity Impacts and Atomic Oxygementioning
confidence: 99%